2007
DOI: 10.1515/bc.2007.039
|View full text |Cite
|
Sign up to set email alerts
|

Human dipeptidyl peptidase III acts as a post-proline-cleaving enzyme on endomorphins

Abstract: Dipeptidyl peptidase III (DPP III) is a zinc exopeptidase with an implied role in the mammalian pain-modulatory system owing to its high affinity for enkephalins and localisation in the superficial laminae of the spinal cord dorsal horn. Our study revealed that this human enzyme hydrolyses opioid peptides belonging to three new groups, endomorphins, hemorphins and exorphins. The enzymatic hydrolysis products of endomorphin-1 were separated and quantified by capillary electrophoresis and the kinetic parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 36 publications
2
62
0
Order By: Relevance
“…In contrast, all subsites in DPP III are deep and somewhat hydrophobic (SI Appendix, Fig. S7 and Table S2), in agreement with the relaxed specificity shown by this enzyme (18).…”
Section: Resultssupporting
confidence: 77%
“…In contrast, all subsites in DPP III are deep and somewhat hydrophobic (SI Appendix, Fig. S7 and Table S2), in agreement with the relaxed specificity shown by this enzyme (18).…”
Section: Resultssupporting
confidence: 77%
“…3). Although DPP III enzymes are known to be quite unspecific with respect to sequence and length variations of the peptide substrates (18,48,49), they strictly cleave off two amino acid residues from the N terminus of their substrate, i.e. they act in a dipeptidyl-peptidase manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, some pharmacological experiments link DPP III with pain regulation mechanisms because low levels of DPP III activity have been observed in the cerebrospinal fluid of individuals suffering from acute pain (16). Similarly, high concentrations of DPP III found in the superficial laminae of rat spinal cord dorsal horn (17), as well as the high in vitro affinity shown by the human enzyme toward important neuropeptides, such as enkephalins and endomorphins (18), also indicate that this hydrolase could play a role in the mammalian pain modulatory system. These findings make DPP III a potential drug target, and efforts toward inhibitor design and synthesis are under way (19).…”
mentioning
confidence: 95%
“…DPP III was purified and biochemically characterized from several human and animal tissues, slime mold, Drosophila and the yeast Saccharomyces cerevisiae 2 . It was shown that this cytosolic enzyme, which is broadly distributed in eukaryotic cells and tissues, in vitro hydrolyzes a number of biologically active peptides, including opioid peptides enkephalins and endomorphins 1,4,5 . Therefore, its contribution in normal intracellular protein catabolism was assumed and the role in the endogenous pain modulation was suggested.…”
Section: Introductionmentioning
confidence: 99%